1978
DOI: 10.1111/j.1467-7717.1978.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis of the 1970 San Antonio Diphtheria Epidemic*

Abstract: Prediction of disease patterns for communicable diseases with low prevalence rates is difficult because of the random variations inherent in the data Smoothing of prevalence or incidence data prior to the analysis may facilitate these predictions. All of the analyses are based on census tract characterisiics. The disadvantages of this type of data are that the boundaries are arbitraty and lead to some heterogenous tracts. Also, the analyses depend totally on aggregate rather than individual data. The advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Nailul et al [16] also identified a negative association between diphtheria incidence and vaccination coverage in East Java, Indonesia in 2010. Furthermore, Quesada [17] found that diphtheria incidence was associated with poverty rates during an outbreak in San Antonio, Texas in 1970.…”
Section: Introductionmentioning
confidence: 99%
“…Nailul et al [16] also identified a negative association between diphtheria incidence and vaccination coverage in East Java, Indonesia in 2010. Furthermore, Quesada [17] found that diphtheria incidence was associated with poverty rates during an outbreak in San Antonio, Texas in 1970.…”
Section: Introductionmentioning
confidence: 99%